Immunisation in the 21st Century: Foundations, Challenges, and Strategic Directions for Global Health - Adumashi, Funke Abolade; Obohwemu, Kennedy Oberhiri; Abayomi, Gabriel Olaoluwa; Kenneth, Iyevhobu Oshiokhayamhe; Ekwuluo, Celestine Emeka; Ituah, Festus (Advances in Social Sciences Research Journal, 2026)
Immunization stands as one of the greatest achievements in global health and development, saving millions of lives each year and reshaping the trajectory of public health. It involves the process of making an individual immune or resistant to a particular disease through the administration of vaccines that stimulate the body’s immune system to recognise and combat pathogens. Historically, immunity could only be acquired by contracting and surviving an infectious disease; however, the development of vaccines has enabled immunity to be safely induced without exposure to the illness itself. Vaccines introduce antigens that mimic those of pathogens, thereby triggering a protective immune response and building immunological memory. Immunization can occur through active or passive mechanisms, while vaccines are broadly classified as live attenuated or inactivated. Despite remarkable global progress, immunization continues to face significant challenges that threaten its sustainability. These include vaccine hesitancy, inequitable access, logistical and infrastructural limitations, and fragmented global coordination. Overcoming these barriers requires a coordinated and multifaceted approach involving governments, international organisations, pharmaceutical companies, civil society, and communities. Strengthening healthcare infrastructure, expanding vaccination across the life course, and integrating immunization into broader health systems are essential to achieving equitable coverage. Sustaining progress also depends on comprehensive public education campaigns that raise awareness about vaccine benefits, counter misinformation, and reinforce public trust in science. Investment in surveillance, cold-chain logistics, and communication strategies will ensure vaccines remain safe, effective, and accessible. Continued global collaboration is vital for maintaining momentum towards universal immunization coverage and achieving the Sustainable Development Goals. Ultimately, immunization represents both a biomedical triumph and a moral imperative — protecting populations, promoting equity, and reaffirming health as a universal human right.